Sport managers in Finland - Seppänen, K.-P. (2020)
The purpose of this Master`s thesis is to study the profiles of the sport managers in Finland at the moment.More specifically the research aim to investigate to what extent the sport manager types defined by Laakso (2016) can be applied in the sport management field in general.For this purpose, a quantitative survey was conducted. An email-survey was sent to 633 managers working in leading sport positions in different sport organizations in Finland. In total 284 answers were received resulting in a response rate of 44.9 percent. As a theoretical framework, Laakso`s (2016) model of sport manager types and paths was used. In generalsport managers in Finland have long and versatile careers in sports and are either chosen forthe position because oftheir management background or because their strong sport background has played a significant role in selection. Results of this study revealed six Finnish sport manager types: chosen, sportsman, politician, bureaucrat, educator, drifterand amateur. Subsequently five sport manager paths can be labelled as:the story of growth,the story of drifting,the story of coincidence,the story of pursuit andthe story of business.In earlier studies sport managers have been found to have high education, educational degree in sport, competitive sport background and on average, 48 years of age. The number of female sport managers has been increasing in recent years, yet still most of the sport managers are men. The results of this study give a comprehensive picture of sport management and managers in Finland, which can be used to develop educational programs as well as a new foundationfor future research.